ACTIVITY TEST LARVASIDES OF FRACTION METANOL-WATER FROM FLOWER (Clitoria ternatea L.) ON Aedes aegypti MOSQUITO LARVA INSTAR III - rahmi nurmala destiani (INDONESIA NATURAL RESEARCH PHARMACEUTICAL JOURNAL, 2019)
Dengue Hemorrhagic Fever is a disease caused by Dengue virus transmitted to humans through the bite of the Aedes aegypti and Aedes albocpictus mosquitoes. Some efforts can be made to prevent DHF, namely, by controlling the vector to break the life cycle of mosquitoes so as to reduce contact between mosquitoes as vectors with humans. Larvaside is a class of pesticides that can kill insects that are not yet mature or as larval killers, but the use of synthetic insecticides for a long time can cause resistance to mosquito larvae or target insects. This study aims to determine the larvicidal activity of methanol-water fraction of telang flower (Clitoria ternatea L.) against larvae of Aedes aegypti instar III. The concentration of methanol-water fraction tested was 4 drops (200mg @ 100ml), 6 drops (300mg @ 100ml), 8 drops (400mg @ 100ml) and 10 drops (500mg @ 100ml), control (-) aquadest and control (+) themephos. Larvicide activity testing is done by weighing each concentration then dissolving it in PAM water containing 25 larvae per @ 100ml each, and each concentration is replicated 4 times. LC50 is obtained in concentrations of 8 drops (400mg @ 100ml) which is 56%. One Way ANOVA statistical analysis test results showed there were significant differences between each concentration in the treatment with a significance level of p <0.05. This means that each concentration of methanol-water fraction has different activity as larvaside against larvae of Aedes aegypti instar III. Keywords: Larvaside; Telang flower (Clitoria ternatea L.); larvae of Aedes aegypti instar III.